ANALISIS PENGARUH KUALITAS SISTEM INFORMASI AKADEMIK TERHADAP KEPUASAN END-USER - Evi Yulianti (Jurnal Informatika Global)
This study examined whether the five instruments developed by Doll and Torkzadeh from previous studies that include (contents, accuracy, format, user convenience, timeliness). Of the five instruments, whether the quality of academic information systems have an influence on the End-User satisfaction. And the factors which indicators of  quality  information  system  of Academic most  influence on  the End-User  satisfaction  in  using the System Academic  information. Data  taken  from the  population  of students  as  stakeholders  of the most widely  used academic information system and the number of samples selected were 303 people from 1246 students active in PTS. XYZ. The collection of data with direct surveys and disseminate questioner. The results showed  that the independent  variables  consist  of  the content,  accuracy,  ease of  use,  and timeliness,  individually  significantly influence  the dependent variable  (Y). While the  format of  the  individual variables had no significant effect on variable Y that is user satisfaction SIA.  Key words: User Satisfaction Information, Academic